DIALEKTIKA INKLUSIVISME DAN EKSKLUSIVISME ISLAM KAJIAN SEMANTIK TERHADAP TAFSIR AL-QURAN TENTANG HUBUNGAN ANTARAGAMA - Nurhadi, Rofiq; Hadi, Syamsul; I. M., Thoyib; Suhandano, Suhandano (Sekolah Pascasarjana UGM, 2013)
Potentially, both inclusivism and exclusivism can emerge from Islam itself. To an extreme point, inclusive point of view underline the importance to apprecieate religious pluralism and to avoid truth claims. To the other extreme, exlusive point of view suspect and even reject pluralism and upholds truth claims. Islam may be presented by the two extremes, and it is not only because of defferent emphasis in reading the holy texts, but also because of defferent methodologies of interpretation being employed. This paper discusses different methodologi of interpretation that determinate significantly the meaning of dÄ«n, millah and syarÄ«âah and how they are related. The one that uses the relation of synonymy avoid taâÄrud al-adillah reading (the dispute among axioms) so leads to inclusive comprehension. The other using the relation of hyponymy between din and syarÄ«âah leads to taâarud reading, uses of nasikh wa al-mansÅ«kh method (abrogation), and so leads to exclusive comprehension.